Olfactory gyrus intracerebral hemorrhage in a patient with COVID-19 infection. (September 2020) - Thu, Sai Si; Matin, Nassim; Levine, Steven R.
Highlights: Since the outbreak with novel corona virus in December 2019, a myriad of different neurological manifestations in patients with COVID-19 infection have been reported. We present a case of non-traumatic intracranial hemorrhage in the olfactory gyrus in a patient who tested positive for SARS-COV-2. The area of hemorrhage is not a common location for spontaneous hemorrhage. Given that loss of smell is considered a relatively common symptom of this pandemic, it is an intriguing association of COVID-19 and olfactory gyrus ICH for neurotropism of SARS-CoV2 for olfactory bulb and glia cells through nasal mucosa. Future studies will need to elucidate the exact mechanism of anosmia from COVID-19 and potential mechanisms leading to ICH. Abstract: Since the outbreak with novel corona virus in December 2019, a myriad of different neurological manifestations in patients with COVID-19 infection have been reported. We present a case of non-traumatic intracranial hemorrhage in the olfactory gyrus in a patient who tested positive for SARS-COV-2. The area of hemorrhage is not a common location for spontaneous hemorrhage. Given that loss of smell is considered a relatively common symptom of this pandemic, it is an intriguing association of COVID-19 and olfactory gyrus ICH for neurotropism of SARS-CoV2 for olfactory bulb and glia cells through nasal mucosa. Future studies will need to elucidate the exact mechanism of anosmia from COVID-19 and potential mechanisms leading to ICH.